Investigating how luxury brands{u2019} sustainable initiatives elevate consumer-level brand happiness, brand evangelism, and well-being - Sabbir, Md. Mahiuddin; Junaid, Muhammad; Levermore, Roger; White, Steven; HM King's Scholarship, Thailand (Pathum Thani : Asian Institute of Technology, 2024)
Sustainability within the luxury domain has evolved from a theoretical idea to an operational imperative. Yet, little is known about consumer reactions to luxury brands{u2019} sustainable initiatives, especially those that hinge on technology-led sustainability and corporate social responsibility (CSR) actions. Addressing this gap, this study investigates how luxury brands{u2019} sustainable initiatives elevate consumer-level brand happiness (BH), brand evangelism (BE), and well-being. Two pertinent psychological factors, namely technology-as-solution belief (TSB) and consumer wisdom (CW), are considered moderators in this investigation. Based on a sample of 363 respondents, the current research reveals that technology-led sustainability and CSR actions positively enhance consumers{u2019} brand attitudes (BA). BA, in turn, contributes to variations in BH, ultimately leading to BE and perceived well-being among consumers. However, the study found no significant moderating effect of TSB, with CW partially moderating the path between CSR actions and BA. Theoretically, this pioneering study substantiates the promising role of the latest technologies as firm-level sustainable initiatives and introduces BH in the sustainable luxury domain. Drawing on this study{u2019}s findings, luxury firms should strategically promote employed technologies as integral components of their sustainable initiatives. Marketers should also craft a subtle, authentic, and genuine storyline to communicate their CSR initiatives and ensure brands{u2019} credibility and appeal to consumers. Despite these contributions, this study has a few limitations paving the way for future research as presented at the end.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2024
Keywords: Luxury goods industry -- Management; Brand name products -- Management